PERSEPSI SISWA SEKOLAH DASAR TERHADAP KEGIATAN LITERASI MEMBACA DENGAN METODE READ ALOUD: UPAYA UNTUK MENINGKATKAN KETERAMPILAN MEMBACA - Neneng Sri Wulan; Wulandari; Dwi Anisa Haftani3 (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article is based on the importance of elementary school students’ abilities as a foundation to comprehend every material, especially for their abilities to understand the content of reading text material they read. One of the methods that can be carried out is to do the reading activity by applying read-aloud. Read aloud is an activity to read aloud applied by parents or teachers to children or students. The research in this article is aimed to determine the students’ abilities to comprehend the content of reading and students' perceptions of the read-aloud. The approach used in the research was qualitative with a descriptive-analysis research method. The data collection techniques were questionnaires and document studies. Respondents of the study involved 44 first-grade elementary school students in Purwakarta. The results showed that the student’s ability to comprehend the reading content was good with an average of 79.76. Students could comprehend the characters, story content, conflict, plot, setting, point of view, and values. Students' perceptions of reading aloud activities are good or positive. A number of 44 students preferred to do the activity of reading aloud. Above all, the reading aloud method could be an alternative activity in reading literacy as a good influence for elementary school students.